The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1128/cvi.00009-07
|View full text |Cite
|
Sign up to set email alerts
|

Protective Meningococcal Capsular Polysaccharide Epitopes and the Role of O Acetylation

Abstract: Previous studies with group C meningococcal polysaccharide-tetanus toxoid (GCMP-TT) conjugates had suggested that the GCMP O-acetyl group masked the protective epitope for group C meningococci through steric hindrance or altered conformations. For this report, we confirmed this phenomenon and performed comparative studies with group Y meningococcal polysaccharide (GYMP)-TT to determine whether it might extend to other serogroups. The de-O-acetylated (dOA) polysaccharides (PSs) resulted in higher serum bacteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 52 publications
(48 reference statements)
0
36
0
Order By: Relevance
“…O-acetylation of CPs has been identified among many pathogenic bacteria, such as Neisseria meningitidis, Salmonella enterica serovar Typhi Vi, and S. pneumoniae, and O-acetyl groups are important immunogenic determinants (34)(35)(36)(37). The S. aureus ⌬cap5H mutant was more susceptible to complement-mediated OPK and less virulent for mice than the isogenic parental strain (24).…”
Section: Figmentioning
confidence: 99%
“…O-acetylation of CPs has been identified among many pathogenic bacteria, such as Neisseria meningitidis, Salmonella enterica serovar Typhi Vi, and S. pneumoniae, and O-acetyl groups are important immunogenic determinants (34)(35)(36)(37). The S. aureus ⌬cap5H mutant was more susceptible to complement-mediated OPK and less virulent for mice than the isogenic parental strain (24).…”
Section: Figmentioning
confidence: 99%
“…In many bacteria, O-acetylation alters the physicochemical properties of capsule by changing the conformation of capsular repeat units (13) or increasing viscosity (14). O-acetylation also alters the host-pathogen interaction by creating immunogenic epitopes (11,13,15), by neutralizing reactive chlorine species (16,17), and/or by mediating resistance to lysozyme and complement deposition (18)(19)(20)(21). Many bacteria have membrane-bound O-acetyltransferases (MOATs) that are thought to attach O-acetyl groups to the capsular repeat unit at the end of the capsular biosynthetic process (22)(23)(24).…”
mentioning
confidence: 99%
“…O acetylation has been shown to be an important parameter when measuring functional antibody activity in meningococcus (2,10). With meningococcus groups C and Y, the O acetylation masks the epitopes on the Ps backbone to which functional antibody is directed (8). Although some investigators (21) have suggested that conjugation of Ps to different carriers can potentially result in the generation of crossreactive antibodies, in the case of unconjugated Ps there is no aid in the presentation of the antigen to the host.…”
mentioning
confidence: 99%